In the given figure, DEFG is a square and ∠BAC = 90°. Show that FG ^{ 2 } = BG × FC
CBSE Class 10 Sample Paper for 2020 Boards - Maths Standard
Question 1 Important
Question 2 Important
Question 3
Question 4 Important
Question 5 Important
Question 6 Important
Question 7
Question 8 Important
Question 9 Important
Question 10
Question 11
Question 12 (OR 1st question)
Question 12 (OR 2nd question)
Question 13 Important
Question 14 Important
Question 15 Important
Question 16
Question 17 Important
Question 18 (OR 1st question) Important
Question 18 (OR 2nd question) Important
Question 19
Question 20
Question 21 Important
Question 22 Important
Question 23 (OR 1st question) Important You are here
Question 23 (OR 2nd question)
Question 24 Important
Question 25 (OR 1st question) Important
Question 25 (OR 2nd question)
Question 26 Important
Question 27 (OR 1st question)
Question 27 (OR 2nd question) Important
Question 28 Important
Question 29 (OR 1st question)
Question 29 (OR 2nd question)
Question 30 Important
Question 31 Important
Question 32 (OR 1st question) Important
Question 32 (OR 2nd question) Important
Question 33 Important
Question 34 Important
Question 35 (OR 1st question) Important
Question 35 (OR 2nd question)
Question 36
Question 37 (OR 1st question)
Question 37 (OR 2nd question)
Question 38 (OR 1st question)
Question 38 (OR 2nd question) Important
Question 39
Question 40 Important
CBSE Class 10 Sample Paper for 2020 Boards - Maths Standard
Last updated at April 16, 2024 by Teachoo
Question 23 (OR 1st question) In the given figure, DEFG is a square and ∠BAC = 90° . Show that FG2 = BG × FC Now, DE ∥ GF, So, we can say DE ∥ BC For parallel lines DE and BC, transversal AB ∠ ADE = ∠ GBD For parallel lines DE and BC, transversal AC ∠ AED = ∠ FCE Now, In Δ ADE and Δ GBD ∠ ADE = ∠ GBD ∠ DAE = ∠ DGB Δ ADE ∼ Δ GBD In Δ ADE and Δ FEC ∠ AED = ∠ FCE ∠ DAE = ∠ EFC Δ ADE ∼ Δ FEC So, we can write Δ GBD ∼ Δ FEC Hence, sides of similar triangle are in proportion 𝐺𝐷/𝐹𝐶=𝐺𝐵/𝐹𝐸 GD × FE = FC × GB Since DEFG is a square GD = FE = FG So, our equation becomes FG × FG = FC × GB FG2 = FC × GB Hence proved